Composite lithium battery diaphragm and preparation method thereof

By using natural clay mineral nanotubes and polyphosphazene resin microspheres in the coating of lithium battery separators, the problems of the membrane being easily contracted, flammable and poor affinity for electrolytes at high temperatures are solved, and better heat is achieved Stability, flame retardancy and electrochemical properties.

CN119518233APending Publication Date: 2025-02-25DONGFENG MOTOR GRP

Patent Information

Application Number
CN202411429051.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing lithium battery separators are prone to shrink and burn at high temperatures, and have poor affinity for electrolytes, resulting in unstable battery performance.

Method used

A composite lithium battery separator is used, and its coating contains natural clay mineral nanotubes and polyphosphazene resin microspheres. Through the synergistic action of these materials, the thermal shrinkage, flame retardant and electrolyte adsorption capacity of the separator are improved.

Benefits of technology

The heat shrinkability of the diaphragm is reduced, the flame retardant performance is improved, the diaphragm is not easy to burn at high temperatures, and the affinity and ionic conductivity are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518233A_ABST
    Figure CN119518233A_ABST
Patent Text Reader

Abstract

The invention relates to a composite lithium battery diaphragm and a preparation method thereof, and belongs to the technical field of lithium batteries. The composite lithium battery diaphragm comprises a polymer base membrane; and the material of the coating comprises a natural clay mineral nanotube and a polyphosphazene resin microsphere. According to the composite lithium battery diaphragm disclosed by the invention, the coating comprises the natural clay mineral nanotube and the polyphosphazene resin microspheres, and the volume change rate of the coating at a high temperature is small, so that the thermal shrinkage of the composite lithium battery diaphragm is reduced; due to the synergistic flame-retardant effect of the natural clay mineral nanotubes and the polyphosphazene resin microspheres, the inflammability of the composite lithium battery diaphragm is improved, and the composite lithium battery diaphragm can be self-extinguished after being ignited; the coating formed by the natural clay mineral nanotubes and the polyphosphazene resin microspheres has abundant pore channels and pores and can absorb a large amount of electrolyte, so that the composite lithium battery diaphragm has high affinity to the electrolyte and high ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a lithium battery, and in particular to a lithium battery separator. Background Art

[0002] With the development of the times and technology, people's demand for consumer electronics, power batteries and energy storage equipment is increasing. Lithium-ion batteries are widely used because of their high energy density and long cycle life. The diaphragm is one of the core materials of lithium-ion batteries. Its main function is to separate the positive and negative electrodes of the battery. It is a thin film with a microporous structure while ensuring the passage of lithium ions. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and affects the capacity and cycle of the battery. At present, polyolefin diaphragms such as polypropylene diaphragms and polyethylene diaphragms are mainly used commercially. These diaphragms have the problem of easy shrinkage when heated. In actual use, when encountering abnormally high temperatures, the diaphragms are prone to melt and shrink, which leads to a large area of ​​short circuit in the battery. At the same time, because the diaphragm itself is flammable, the accumulated heat of the battery short circuit is easy to further cause the diaphragm to burn, which will cause uncontrollable serious consequences. In addition, the affinity of existing lithium battery diaphragms to electrolytes needs to be improved. Summary of the invention

[0003] The embodiments of the present application provide a composite lithium battery separator and a preparation method thereof to solve the technical problems that the existing lithium battery separators are easy to shrink when heated, easy to burn, and have poor affinity for electrolyte.

[0004] In a first aspect, an embodiment of the present application provides a composite lithium battery separator, the composite lithium battery separator comprising:

[0005] polymer-based films;

[0006] The coating layer coated on the polymer base film comprises natural clay mineral nanotubes and polyphosphazene resin microspheres.

[0007] In some embodiments of the present application, in the coating, the mass ratio of the natural clay mineral nanotubes to the polyphosphazene resin microspheres is 1:0.5-20.

[0008] In some embodiments of the present application, the particle size of the microspheres satisfies: 0.05 μm ≤ D50 ≤ 5 μm; and / or,

[0009] The specific surface area of ​​the natural clay mineral nanotubes is 10 to 200 m 2 / g; and / or,

[0010] The natural clay mineral nanotube is at least one of attapulgite nanotube and halloysite nanotube.

[0011] In some embodiments of the present application, the coating further includes a dispersant, a wetting agent and a binder.

[0012] In some embodiments of the present application, the dispersant and the wetting agent are each independently selected from at least one of the following compounds: fluoroalkyl methoxy alcohol ether, polyoxyethylene alkylamine, sodium methylene bisnaphthalene sulfonate, polyether modified silicone, sodium aryl naphthalene sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium perfluorooctanoate, nonylphenol polyoxyethylene ether, sodium butyl naphthalene sulfonate, polyacrylate, polyethylene glycol, sodium carboxymethyl cellulose; and / or,

[0013] The binder is at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, lithium polyacrylate, and polyacrylonitrile multipolymer.

[0014] In some embodiments of the present application, the composite lithium battery separator has the following properties:

[0015] After baking at 180℃ for 30min, the thermal shrinkage is ≤5%;

[0016] Air permeability: 99.6~403.6s / 100mL;

[0017] The electrolyte absorption rate is 120.6-469.2%;

[0018] The ionic conductivity is 0.5~3.5mS / cm.

[0019] In a second aspect, an embodiment of the present application provides a method for preparing a composite lithium battery separator, wherein the composite lithium battery separator is the composite lithium battery separator described in any embodiment of the first aspect, and the method for preparing the composite lithium battery separator comprises the following steps:

[0020] Provide natural clay mineral nanotubes;

[0021] preparing polyphosphazene resin microspheres;

[0022] Dispersing the natural clay mineral nanotubes and polyphosphazene resin microspheres in water to prepare a slurry;

[0023] Providing a polymer base film, and coating the slurry on the polymer base film;

[0024] The polymer-based film is dried to obtain the composite lithium battery separator.

[0025] In some embodiments of the present application, the preparation of polyphosphazene resin microspheres comprises the following steps:

[0026] dispersing hexachlorotriphosphazene and monomers in a solvent;

[0027] Adding a catalyst to the solvent to obtain a mixed solution after reaction;

[0028] The mixed liquid is subjected to solid-liquid separation to obtain the polyphosphazene resin microspheres,

[0029] The monomer is at least one of 4,4-dihydroxydiphenyl sulfone, 4,4-diaminodiphenyl ether, 4,4-dihydroxybenzophenone, p-diphenylamine, 4,4-diaminodiphenyl ether, 3,4-dihydroxybenzoic acid, phloroglucinol, melamine, p-phenylenediamine, hexafluorobisphenol A, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, dopamine, phloretin, resveratrol, and isosorbide.

[0030] In some embodiments of the present application, the natural clay mineral nanotubes and polyphosphazene resin microspheres are dispersed in water, and a dispersant, a wetting agent and a binder are also added to the water.

[0031] In some embodiments of the present application, the total mass of the dispersant, the wetting agent and the binder accounts for 1% to 10% of the mass of the slurry; and / or,

[0032] The mass ratio of the total mass of the natural clay mineral nanotubes and the polyphosphazene resin microspheres to water is 1:1.5-50.

[0033] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0034] The composite lithium battery separator provided in the embodiment of the present application has a coating comprising natural clay mineral nanotubes and polyphosphazene resin microspheres, and the volume change rate of the coating at high temperature is small, which reduces the thermal shrinkage of the composite lithium battery separator; the synergistic flame retardant effect of the natural clay mineral nanotubes and the polyphosphazene resin microspheres improves the flammability of the composite lithium battery separator, and can also achieve self-extinguishing after ignition; the coating formed by the natural clay mineral nanotubes and the polyphosphazene resin microspheres has abundant channels and pores, and can absorb a large amount of electrolyte, so that the composite lithium battery separator has a high affinity for the electrolyte and a high ionic conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0036] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0037] Figure 1A scanning electron microscope photograph of a composite lithium battery separator provided in an embodiment of the present application;

[0038] Figure 2 A scanning electron microscope photograph of a polyethylene diaphragm provided as a comparative example of the present application;

[0039] Figure 3 A morphological comparison diagram of the composite lithium battery separator provided in the embodiment and the polyethylene separator provided in the comparative example before and after heating;

[0040] Figure 4 The photos are recording the combustion phenomena of the composite lithium battery separator provided in the embodiment and the polyethylene separator provided in the comparative example. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0042] Unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. In the event of a conflict, this specification takes precedence.

[0043] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0044] Existing lithium battery separators have technical problems such as easy shrinkage when heated, easy combustion, and poor affinity for electrolyte.

[0045] The technical solution provided by the embodiments of the present application is to solve the above technical problems, and the overall idea is as follows:

[0046] In a first aspect, an embodiment of the present application provides a composite lithium battery separator, the composite lithium battery separator comprising:

[0047] polymer-based films;

[0048] The coating layer coated on the polymer base film comprises natural clay mineral nanotubes and polyphosphazene resin microspheres.

[0049] It is easy to understand that the polymer-based membrane is a conventional product in the field of lithium battery separators and can be purchased commercially.

[0050] It is easy to understand that the main flame retardant principle of the natural clay mineral nanotubes is that they produce water and isolate oxygen when they are decomposed by heat, and the main flame retardant principle of the polyphosphazene resin microspheres is that the thermal decomposition is an endothermic reaction, which can buffer temperature changes, and produce non-combustible substances such as phosphoric acid after thermal decomposition. The boiling point of water is relatively low, and the temperature of the natural clay mineral nanotubes when they are thermally decomposed will usually directly produce water vapor, which has a large volume and can quickly dilute or isolate oxygen. Therefore, the flame retardant function of the natural clay mineral nanotubes will take effect quickly at high temperatures, buying reaction time for the thermal decomposition of the polyphosphazene resin microspheres.

[0051] It is easy to understand that the chemical reaction between the polyphosphazene resin microspheres and the natural clay mineral nanotubes at high temperature can absorb heat, and the reaction product can be flame retardant, which is beneficial to reducing the thermal shrinkage of the composite lithium battery separator.

[0052] It is easy to understand that a large number of pores will be formed between the polyphosphazene resin microspheres, and between the polyphosphazene resin microspheres and the clay mineral nanotubes. These pores are small in size, have high surface tension, and have strong adsorption capacity for electrolytes. The clay mineral nanotubes can also provide additional channels between these pores, which on the one hand further enhance the adsorption capacity of the electrolyte, and on the other hand provide additional ion pathways, which are beneficial to increase the ion conductivity of the composite lithium battery separator. In addition, the total volume of the pores is not large relative to the total volume of the polyphosphazene resin microspheres and the clay mineral nanotubes, which enables the flame retardant substances released by the thermal decomposition of the polyphosphazene resin microspheres and the clay mineral nanotubes to quickly fill the pores, effectively dilute the electrolyte and oxygen, and thus flame retardant.

[0053] The composite lithium battery separator described in the present application has a coating comprising natural clay mineral nanotubes and polyphosphazene resin microspheres, and the volume change rate of the coating at high temperature is small, which reduces the thermal shrinkage of the composite lithium battery separator; the synergistic flame retardant effect of the natural clay mineral nanotubes and the polyphosphazene resin microspheres improves the flammability of the composite lithium battery separator, and can also achieve self-extinguishing after ignition; the coating formed by the natural clay mineral nanotubes and the polyphosphazene resin microspheres has abundant channels and pores, and can absorb a large amount of electrolyte, so that the composite lithium battery separator has a high affinity for the electrolyte and a high ionic conductivity.

[0054] In some embodiments of the present application, in the coating, the mass ratio of the natural clay mineral nanotubes to the polyphosphazene resin microspheres is 1:0.5-20.

[0055] The beneficial effect of the mass ratio of the natural clay mineral nanotubes to the polyphosphazene resin microspheres being 1:0.5-20 is that the thermal shrinkage of the composite lithium battery separator can be significantly reduced while maintaining sufficient flexibility and processability of the composite lithium battery separator.

[0056] In some embodiments of the present application, the particle size of the microspheres satisfies: 0.05 μm ≤ D50 ≤ 5 μm; and / or,

[0057] The specific surface area of ​​the natural clay mineral nanotubes is 10 to 200 m 2 / g; and / or,

[0058] The natural clay mineral nanotube is at least one of attapulgite nanotube and halloysite nanotube.

[0059] The beneficial effect of the particle size of the microspheres meeting the above conditions is that the pore structure between the microspheres is small enough, the adsorption capacity of the electrolyte is strong enough, and the microspheres are not easily agglomerated.

[0060] As an example, the D50 of the microspheres may be 0.05 μm, 0.2 μm, 1 μm, 3 μm, or 5 μm.

[0061] The specific surface area of ​​the natural clay mineral nanotubes is 10 to 200 m 2 The beneficial effect of the natural clay mineral nanotubes is that the natural clay mineral nanotubes can not only fully absorb the electrolyte and transmit ions, but also fully support the coating and reduce the thermal shrinkage of the composite lithium battery separator.

[0062] As an example, the specific surface area of ​​the natural clay mineral nanotubes may be 10 m 2 / g, 50m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g.

[0063] The beneficial effect of selecting at least one of attapulgite nanotubes and halloysite nanotubes as the natural clay mineral nanotubes is that attapulgite nanotubes and halloysite nanotubes have good flame retardant properties, have a strong supporting effect on the coating, and are cheap and easily available in the market.

[0064] In some embodiments of the present application, the coating further includes a dispersant, a wetting agent and a binder.

[0065] In some embodiments of the present application, the dispersant and the wetting agent are each independently selected from at least one of the following compounds: fluoroalkyl methoxy alcohol ether, polyoxyethylene alkylamine, sodium methylene bisnaphthalene sulfonate, polyether modified silicone, sodium aryl naphthalene sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium perfluorooctanoate, nonylphenol polyoxyethylene ether, sodium butyl naphthalene sulfonate, polyacrylate, polyethylene glycol, sodium carboxymethyl cellulose; and / or,

[0066] The binder is at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, lithium polyacrylate, and polyacrylonitrile multipolymer.

[0067] It is easy to understand that the coating is usually formed by coating a slurry, and the coating described in the present application can be prepared by a slurry using water as a solvent. The above-mentioned dispersant is used to increase the dispersibility of the polyphosphazene resin microspheres in water, and the wetting agent is used to increase the wetting ability of the polyphosphazene resin microspheres to water.

[0068] The binder is used to increase the film-forming ability of the natural clay mineral nanotubes and the polyphosphazene resin microspheres.

[0069] In some embodiments of the present application, the composite lithium battery separator has the following properties:

[0070] After baking at 180℃ for 30min, the thermal shrinkage is ≤5%;

[0071] Air permeability: 99.6~403.6s / 100mL;

[0072] The electrolyte absorption rate is 120.6-469.2%;

[0073] The ionic conductivity is 0.5~3.5mS / cm.

[0074] In a second aspect, an embodiment of the present application provides a method for preparing a composite lithium battery separator, wherein the composite lithium battery separator is the composite lithium battery separator described in any embodiment of the first aspect, and the method for preparing the composite lithium battery separator comprises the following steps:

[0075] S1: Provide natural clay mineral nanotubes;

[0076] S2: preparing polyphosphazene resin microspheres;

[0077] S3: dispersing the natural clay mineral nanotubes and polyphosphazene resin microspheres into water to prepare a slurry;

[0078] S4: providing a polymer base film, and coating the slurry on the polymer base film;

[0079] S5: Drying the polymer base film to obtain the composite lithium battery separator.

[0080] In some embodiments of the present application, the preparation of polyphosphazene resin microspheres comprises the following steps:

[0081] S21: dispersing hexachlorotriphosphazene and monomers in a solvent;

[0082] S22: adding a catalyst to the solvent to obtain a mixed solution after reaction;

[0083] S23: performing solid-liquid separation on the mixed liquid to obtain the polyphosphazene resin microspheres,

[0084] The monomer is at least one of 4,4-dihydroxydiphenyl sulfone, 4,4-diaminodiphenyl ether, 4,4-dihydroxybenzophenone, p-diphenylamine, 4,4-diaminodiphenyl ether, 3,4-dihydroxybenzoic acid, phloroglucinol, melamine, p-phenylenediamine, hexafluorobisphenol A, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, dopamine, phloretin, resveratrol, and isosorbide.

[0085] Those skilled in the art will appreciate that the catalyst is an inorganic base or an organic base. In some embodiments of the present application, the catalyst is at least one of sodium hydroxide, triethylamine, and diisopropylethylamine. In some embodiments of the present application, the solvent in step S21 is at least one of tetrahydrofuran, acetone, acetonitrile, N,N-dimethylformamide, and dimethyl sulfoxide. In some embodiments of the present application, after the implementation of step S21, the concentration of the hexachlorotripolyphosphazene in the solvent is 1 to 20 mmol / L, and the concentration of the monomer in the solvent is 3 to 60 mmol / L. In some embodiments of the present application, the reaction time in step S22 is 0.2 to 2h. In some embodiments of the present application, after obtaining the polyphosphazene resin microspheres in step S23, the polyphosphazene resin microspheres are also washed, and the washing solvent can be at least one of deionized water and ethanol.

[0086] In some embodiments of the present application, the natural clay mineral nanotubes and polyphosphazene resin microspheres are dispersed in water, and a dispersant, a wetting agent and a binder are also added to the water.

[0087] In some embodiments of the present application, the total mass of the dispersant, the wetting agent and the binder accounts for 1% to 10% of the mass of the slurry; and / or,

[0088] In the slurry, the mass ratio of the total mass of the natural clay mineral nanotubes and the polyphosphazene resin microspheres to water is 1:1.5-50.

[0089] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.

[0090] Example

[0091] This embodiment provides a composite lithium battery separator, which is prepared by the following method:

[0092] Synthesis of polyphosphazene microspheres:

[0093] Dissolve hexachlorotripolyphosphazene and 4,4-dihydroxydiphenyl sulfone in a reaction flask filled with anhydrous acetonitrile at a molar ratio of 1:3, and set the hexachlorotripolyphosphazene monomer concentration to 8 mmol / L. Place the above mixed solution in an ultrasonic cleaning tank with an ultrasonic power of 350 W until the solid powder is completely dissolved;

[0094] The reaction flask was transferred to a water bath, and the temperature was set to 30°C. After 5 minutes, a certain volume of triethylamine was added, and the volume ratio of triethylamine to acetonitrile was 1:50. Stirring was continued for 15 minutes to obtain a suspension of polyphosphazene microspheres, and the reaction was stopped;

[0095] The suspension in the reaction flask was transferred to a centrifuge tube and centrifuged at 13,000 revolutions per minute for 3 minutes using a high-speed centrifuge. The obtained precipitate was washed alternately with deionized water and ethanol twice. The product was transferred to an oven at 80° C. and dried for 12 hours to obtain polyphosphazene microspheres.

[0096] Preparation of coating slurry:

[0097] 70 parts by weight of polyphosphazene microsphere powder, 30 parts by weight of halloysite nanotubes, and water were prepared into a suspension with a solid content of 11%. Subsequently, 2% by weight of a naphthalenesulfonic acid dispersant and 1% of a sodium dodecylbenzenesulfonate wetting agent were added, and after being transferred to a magnetic stirrer and stirred for 24 hours, 5% of a polyacrylonitrile binder was added, and stirring was continued for 6 hours to obtain a coating slurry of polyphosphazene microspheres and halloysite nanotubes.

[0098] Preparation of composite lithium battery separator:

[0099] The polymer base film is a commercial polyethylene diaphragm with a thickness of about 10 μm. The polyethylene diaphragm does not require any special treatment before coating, and only needs to ensure that the surface of the diaphragm is clean.

[0100] The slurry was evenly coated on the polyethylene diaphragm by an automatic coating machine to obtain a composite wet film, which was placed at room temperature of 25°C for 30 minutes. After there was no water mark on the surface of the composite wet film, it was transferred to a blast oven at 80°C for vacuum drying for 10 minutes to obtain a polyethylene composite diaphragm coated with polyphosphazene microspheres and halloysite nanotubes on one side. The above steps were repeated to obtain a polyethylene composite diaphragm coated with flame retardant materials on both sides, i.e., the composite lithium battery diaphragm. The average thickness of the obtained composite lithium battery diaphragm was 18 μm.

[0101] Comparative Example

[0102] This comparative example provides the polyethylene separator used in the examples.

[0103] Related experiments and effect data:

[0104] The air permeability of the composite lithium battery separator in the embodiment was tested using the American Gurley 4110N air permeability tester. The air permeability of the lithium battery separator reflects the tortuosity of the internal pores of the separator and the true path of ion diffusion, which is usually proportional to the ion conductivity and can be evaluated by the Gurley value. The Gurley value refers to the time required for a certain amount of air to pass through a unit area of ​​the separator at a certain specified pressure, in seconds. The composite lithium battery separator in the embodiment has a permeability of 220±10s per 100mL, which has good air permeability.

[0105] The surface morphology of the composite lithium battery separator provided in the embodiment and the polyethylene separator provided in the comparative example was observed under a cold field scanning electron microscope. Figure 1 as well as Figure 2 , Figure 1 This is a scanning electron microscope photo of the composite lithium battery separator in the embodiment. Figure 2 This is a scanning electron microscope photo of the polyethylene diaphragm in the comparative example. Figure 1 and Figure 2 It can be seen that the surface morphology of the composite lithium battery separator provided in the embodiment and the polyethylene separator provided in the comparative example is completely different. For the surface of the composite lithium battery separator provided in the embodiment, the polyphosphazene microspheres and the halloysite nanotubes are staggered, and the ball-and-stick coating formed by them evenly covers the polymer base film, indicating that the slurry formula has good coatability for polyolefin separators. In addition, there are a large number of pores on the coating, which absorb electrolytes and provide abundant channels for the transmission of lithium ions.

[0106] The composite lithium battery separator provided in the embodiment and the polyethylene separator provided in the comparative example were cut into a plurality of discs with a diameter of 16.5 mm using a cutting machine. For the convenience of the following description, the discs cut from the composite lithium battery separator provided in the embodiment are denoted as PZN-HNTs@PE, and the discs cut from the polyethylene separator provided in the comparative example are denoted as PE.

[0107] The PZN-HNTs@PE was weighed one by one and the average value was calculated. The surface density of the composite lithium battery separator provided in the embodiment was calculated to be 11.5±0.5 g / m 2 The thickness of the separator was tested using a handheld thickness gauge, and the average thickness of the composite lithium battery separator provided in the embodiment was 18 μm.

[0108] The liquid absorption rate of the composite lithium battery separator provided in the embodiment and the polyethylene separator provided in the comparative example was tested by the weighing method, that is, the liquid absorption rate of the separator was calculated by the change in weight before and after the separator absorbed liquid: PZN-HNTs@PE and PE were weighed respectively, and then immersed in liquid electrolyte for 1 hour, and then taken out and gently wiped off the surface liquid with filter paper and weighed. The liquid absorption rate EU was calculated using the following formula:

[0109] EU(%)=(W2-W1) / W1×100%

[0110] Among them, W1 and W2 are the masses of the disc before and after being immersed in the electrolyte. The solvent of the test electrolyte is formed by mixing ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7. The solute of the test electrolyte is lithium hexafluorophosphate with a concentration of 1 mol / L. The electrolyte absorption rates of the composite lithium battery separator provided in the embodiment and the polyethylene separator provided in the comparative example are 249% and 164%, respectively.

[0111] The bulk impedance of the composite lithium battery separator provided in the embodiment and the polyethylene separator provided in the comparative example was tested on an electrochemical workstation (Bio-Logic VSP-300) by electrochemical impedance spectroscopy (EIS), and the ionic conductivity was calculated. PZN-HNTs@PE and PE were assembled into stainless steel symmetric cells for testing, with a frequency range of 10 6 ~10 -1 Hz, AC amplitude is 10mV, and the ionic conductivity calculation formula is as follows:

[0112] σ=D / RS

[0113] Wherein, σ represents the ionic conductivity of the membrane; D represents the thickness of the membrane; R is the horizontal axis intercept of the Nyquist plot; S represents the area of ​​the membrane, and the composite lithium battery membrane provided in the embodiment and the polyethylene membrane provided in the comparative example are measured to be 0.64 mS / cm and 0.29 mS / cm, respectively.

[0114] PZN-HNTs@PE and PE were heated at 180 °C for 30 min, respectively, and photos were taken before and after heating to record the morphology of the discs. Figure 3 This is a morphology comparison diagram of the composite lithium battery separator provided in the embodiment and the polyethylene separator provided in the comparative example before and after heating. Figure 3The red circle in the middle is a circle with a diameter of 16.5 mm, PE-180℃ is a morphological photograph of PE after heating at 180℃ for 30 min, and PZN-HNTs@PE-180℃ is a morphological photograph of PZN-HNTs@PE after heating at 180℃ for 30 min. Figure 3 It can be seen that the polyethylene separator provided in the comparative example has obviously undergone a process of shrinkage, melting and then solidification, changing from a round shape to a tiny light white plastic mass, while the composite lithium battery separator provided in the embodiment has basically no obvious shrinkage after heating. This shows that the organic-inorganic resin composite separator obtained in the embodiment of the present invention can have very excellent thermal dimensional stability.

[0115] Using a cutting machine, PZN-HNTs@PE and PE were burned separately on the flame of an alcohol lamp. After ignition, the discs were moved out of the flame range and the burning phenomenon was recorded by a digital camera. Figure 4 The combustion phenomenon of the composite lithium battery separator provided in the embodiment and the polyethylene separator provided in the comparative example is recorded in the photograph. Figure 4 It can be seen that the polyethylene diaphragm provided in the comparative example shrinks when it approaches the flame, shrinks rapidly into a ball the moment it contacts the flame, and then burns out; while the composite lithium battery diaphragm provided in the embodiment does not shrink significantly when it contacts the flame, and can maintain its basic shape. After leaving the flame, the burning part begins to carbonize, and then the burning flame becomes smaller until it goes out. Thanks to the synergistic effect of natural clay mineral nanotubes and polyphosphazene resin microspheres, a protective layer with a dense structure is formed on the surface and inside of the coating, which effectively isolates oxygen and inhibits further combustion of the polymer-based film, thereby exhibiting excellent flame retardancy.

[0116] In summary, relative to the comparative example, the composite lithium battery separator provided in the embodiment has a coating comprising natural clay mineral nanotubes and polyphosphazene resin microspheres, and the volume change rate of the coating at high temperature is small, which reduces the thermal shrinkage of the composite lithium battery separator; the synergistic flame retardant effect of natural clay mineral nanotubes and polyphosphazene resin microspheres improves the flammability of the composite lithium battery separator, and can also achieve self-extinguishing after ignition; the coating formed by natural clay mineral nanotubes and polyphosphazene resin microspheres has abundant channels and pores, and can absorb a large amount of electrolyte, so that the composite lithium battery separator has a high affinity for the electrolyte and a high ionic conductivity.

[0117] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0118] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". Moreover, the terms "including", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "including..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. For the association relationship of more than three associated objects described by "and / or", it means that any one of these three associated objects can exist alone, or any at least two of them exist at the same time. For example, for A, and / or B, and / or C, it can be represented that any one of A, B, and C exists alone, or any two of them exist at the same time, or three of them exist at the same time. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "the following at least one (individual)" or similar expressions refer to any combination of these items, including any combination of single items (individuals) or plural items (individuals). For example, "at least one (individual) of a, b, or c", or "at least one (individual) of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, wherein a, b, c can be single or multiple respectively. The "number of parts" involved in this application, such as weight parts, mass parts, etc., represent the proportional relationship between each component. In the proportional relationship involved in the present application, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond one-to-one with the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.

[0119] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A composite lithium battery separator, characterized in that: The composite lithium battery separator comprises: polymer-based films; The coating comprises natural clay mineral nanotubes and polyphosphazene resin microspheres.

2. The composite lithium battery separator according to claim 1, characterized in that: In the coating, the mass ratio of the natural clay mineral nanotubes to the polyphosphazene resin microspheres is 1:0.5-20.

3. The composite lithium battery separator according to claim 1, characterized in that: The particle size of the microspheres satisfies: 0.05 μm ≤ D50 ≤ 5 μm; and / or, The specific surface area of ​​the natural clay mineral nanotubes is 10 to 200 m 2 / g; and / or, The natural clay mineral nanotube is at least one of attapulgite nanotube and halloysite nanotube.

4. The composite lithium battery separator according to claim 1, characterized in that: The coating also includes a dispersant, a wetting agent and a binder.

5. The composite lithium battery separator according to claim 4, characterized in that: The dispersant and the wetting agent are each independently selected from at least one of the following compounds: fluoroalkyl methoxy alcohol ether, polyoxyethylene alkylamine, sodium methylene bisnaphthalene sulfonate, polyether modified silicone, sodium aryl naphthalene sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium perfluorooctanoate, nonylphenol polyoxyethylene ether, sodium butylnaphthalene sulfonate, polyacrylate, polyethylene glycol, sodium carboxymethyl cellulose; and / or, The binder is at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, lithium polyacrylate, and polyacrylonitrile multipolymer.

6. The composite lithium battery separator according to any one of claims 1 to 5, characterized in that: The composite lithium battery separator has the following properties: After baking at 180℃ for 30min, the thermal shrinkage is ≤5%; Air permeability: 99.6~403.6s / 100mL; The electrolyte absorption rate is 120.6-469.2%; The ionic conductivity is 0.5~3.5mS / cm.

7. A method for preparing a composite lithium battery separator, characterized in that: The composite lithium battery separator is the composite lithium battery separator according to any one of claims 1 to 5, and the preparation method of the composite lithium battery separator comprises the following steps: Provide natural clay mineral nanotubes; preparing polyphosphazene resin microspheres; Dispersing the natural clay mineral nanotubes and polyphosphazene resin microspheres in water to prepare a slurry; Providing a polymer base film, and coating the slurry on the polymer base film; The polymer-based film is dried to obtain the composite lithium battery separator.

8. The method for preparing a composite lithium battery separator according to claim 7, characterized in that: The method for preparing polyphosphazene resin microspheres comprises the following steps: dispersing hexachlorotriphosphazene and monomers in a solvent; Adding a catalyst to the solvent to obtain a mixed solution after reaction; The mixed liquid is subjected to solid-liquid separation to obtain the polyphosphazene resin microspheres, The monomer is at least one of 4,4-dihydroxydiphenyl sulfone, 4,4-diaminodiphenyl ether, 4,4-dihydroxybenzophenone, p-diphenylamine, 4,4-diaminodiphenyl ether, 3,4-dihydroxybenzoic acid, phloroglucinol, melamine, p-phenylenediamine, hexafluorobisphenol A, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, dopamine, phloretin, resveratrol, and isosorbide.

9. The method for preparing a composite lithium battery separator according to claim 7, characterized in that: The natural clay mineral nanotubes and polyphosphazene resin microspheres are dispersed in water, and a dispersant, a wetting agent and a binder are added to the water.

10. The method for preparing a composite lithium battery separator according to claim 9, characterized in that: The total mass of the dispersant, wetting agent and binder accounts for 1% to 10% of the mass of the slurry; and / or, In the slurry, the mass ratio of the total mass of the natural clay mineral nanotubes and the polyphosphazene resin microspheres to water is 1:1.5-50.

Citation Information

Patent Citations

  • Separator / intermediate layer laminate, structure for nonaqueous electrolyte secondary batteries, and aqueous latex

    CN107431172A

  • High-temperature-resistant polymer microsphere coating modified composite diaphragm and preparation method thereof

    CN114497899A

  • Flame retardant, flame-retardant modified diaphragm, battery and preparation methods of flame retardant and flame-retardant modified diaphragm

    CN114865228A

  • PZS-coated SiO2 composite material as well as preparation method and application thereof

    CN115764168A

  • Modified composite diaphragm and preparation method thereof

    CN116315437A

Cited By

  • Composite lithium battery separator and preparation method therefor

    WO2026082022A1